Midkine Serum Levels in Inflammatory and Non-Inflammatory Dilated Cardiomyopathy - Ulrich Grabmaier; Bartolo Ferraro; Kristin Lehnert; Astrid Petersmann; Stephan B. Felix; Ludwig T. Weckbach (Biomedicines)
Objectives: This retrospective study examines midkine, an inflammatory cytokine, as a potential serological biomarker to distinguish dilated cardiomyopathy (DCM) and inflammatory dilated cardiomyopathy (DCMi). Identifying such a biomarker is crucial for effective treatment of these two entities. Methods: The study included 54 patients with heart failure, reduced left ventricular systolic function, and suspected cardiac inflammation. Endomyocardial biopsies were obtained from all 54 patients to differentiate between DCM and DCMi. Blood sera were collected from these patients the same day the endomyocardial biopsy was performed and compared with those of 13 age-matched healthy individuals for different measurements such as midkine and NT-proBNP. Patients were followed up to a median of 194 days after the baseline visit. Results: Endomyocardial biopsies from patients with DCMi were associated with more infiltrating immune cells such as CD68+ macrophages and CD3+ T cells and a more frequent presence of a viral genome than those from patients with DCM. Both groups showed similar improvements in LV function and dimensions over time. MK serum levels were significantly higher in DCM/ DCMi patients than in healthy individuals but did not differ significantly between DCM and DCMi. MK levels did not significantly correlate with NYHA class, NT-proBNP, LVEDD, or LVEF, except for a weak correlation with LVEF at follow-up. Conclusions: Midkine serum levels were significantly higher in patients with a DCM phenotype and severely reduced systolic function. However, these levels could not distinguish between DCM and DCMi and showed no correlation with baseline or follow-up parameters. Therefore, midkine cannot be used as a biomarker to distinguish between DCM and DCMi.